2002
DOI: 10.1002/jcb.10208
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells and neuro‐oncology: Quo vadis?

Abstract: Conventionally, gliomas are assumed to arise via transformation of an intraparenchymal glial cell that forms a mass that then expands centrifugally, eventually invading surrounding tissues. We propose an alternative model in which gliomas arise via initiation and promotion of cells within the brain's subependymal layer or subventricular zone, the source of a recently characterized pool of neural cells with the properties of self-renewal and multipotentiality (i.e., stem cells) that persists into adulthood. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 62 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…We found that HiB5 also inhibited the outgrowth of N32 glioma cells, but animals coinoculated with N25 and HiB5 had a rapid tumor progression showing no difference in survival compared with the control animals inoculated with N25 alone. We have no explanation at present as to why the observed inhibition of tumor growth seems to be dependent on the glioma model used, but many gliomas could be of neural progenitor origin themselves (36). This indicates the possibility that neural progenitor cells situated near or in direct contact with glioma cells could influence the proliferative potential and differentiation status of the glioma cells by signals originating from the differentiating neural progenitor cell line HiB5 or ST14A.…”
Section: Discussionmentioning
confidence: 92%
“…We found that HiB5 also inhibited the outgrowth of N32 glioma cells, but animals coinoculated with N25 and HiB5 had a rapid tumor progression showing no difference in survival compared with the control animals inoculated with N25 alone. We have no explanation at present as to why the observed inhibition of tumor growth seems to be dependent on the glioma model used, but many gliomas could be of neural progenitor origin themselves (36). This indicates the possibility that neural progenitor cells situated near or in direct contact with glioma cells could influence the proliferative potential and differentiation status of the glioma cells by signals originating from the differentiating neural progenitor cell line HiB5 or ST14A.…”
Section: Discussionmentioning
confidence: 92%
“…It would be interesting to investigate the potential correlation between AQP4 expression and the maintenance of an immature glial phenotype by adult astrocytes in vitro, also in view of the fact that adult SVZ stem cells have been shown to derive from radial glia (Merkle et al, 2004) and that putative stem cells have been described in the human adult brain that display glial morphology and antigenic properties (Sanai et al, 2004). These periventricular glia-like neural stem cells and their progeny might be implicated in the generation of brain tumors (Rubinstein et al, 1984;Recht et al, 2003), as well as in the process of endogenous brain repair (Fallon et al, 2000;Nakatomi et al, 2002). Thus, a better characterization of these cells in terms of their water homeostasis dynamics might be critical for the development of potential therapeutic approaches for CNS disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Given their ability to proliferate, self-renew, and migrate, these cells have also the potential to undergo neoplastic transformation (Recht et al, 2003), and a large body of evidence supports this concept, although the identity of the transformed cells is not well defined (Rao, 1999;Holland, 2000;Berger et al, 2004;Jang et al, 2004). Four distinct cell types reside in the adult SVZ (Doetsch et al, 1997(Doetsch et al, , 1999a.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of SVZ cells in the genesis of glioblastomas (Recht et al, 2003) has been suggested by the isolation of neurosphere-forming cells from human glioblastomas (Ignatova et al, 2002) and by studies on transgenic mice (Holland, 2000) and on animals prenatally exposed to the mutagen N-ethyl-Nnitrosourea (ENU) (Oda et al,1997;Leonard et al, 2001;Slikker et al, 2004;Savarese et al, 2005).…”
Section: Introductionmentioning
confidence: 99%